Ecological Ethics in Islamic Banks' Financial Statements and Their Impact on the Sustainable Economy - Yopi Yudha Utama; Mutafarida, Binti; Yuliani, Yuliani; Sariati, Ning Purnama (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2025)
This research aims to analyse the role of ecological ethics in the financial statements of Islamic banks and its implications for sustainable economic development. Building on the foundation of maqāṣid al-sharī‘ah, which emphasises justice, balance, and environmental protection, this research develops a conceptual framework that integrates stakeholder theory, the triple bottom line, and ESG principles within the context of Islamic finance. The method used is a qualitative-descriptive approach with a critical analysis of international and national literature, as well as the development of a conceptual model that explains the relationship between ecological accountability, reporting transparency, and economic stability. The research findings indicate that integrating ecological ethics into financial reports can strengthen the legitimacy of Islamic banks, increase investor confidence, and contribute significantly to the Sustainable Development Goals (SDGs). However, there is still a gap between formalistic reporting practices and the normative ideals of ecological ethics, which has the potential to lead to the risk of greenwashing. This research recommends the need for more inclusive regulations regarding ecological aspects in Sharia reporting standards, as well as encouraging the strengthening of digital innovation for more accountable transparency. This finding enriches the literature on Islamic financial accountability and provides a basis for public policy in strengthening the role of Islamic banks in the sustainable economic ecosystem